EPPO Contingency Exercise Workshop for a Forestry Pest, Zlatibor, Serbia, 2018‐11‐27/29. (24th July 2019) - Tanner, R.; Orlinski, A.; Meyer, J.; Ward, M.; Lukić, S.; Glavendekić, M.; McCann, D.
Abstract : An EPPO Contingency Planning Workshop for a Forestry Pest was held in Zlatibor, Serbia, between 27 and 29 November 2018. In total, 55 experts from 21 EPPO member countries attended the 3‐day workshop. Participants were split into four groups for the exercise and each group acted as an 'outbreak management team' for a scenario based on the finding of a quarantine pest for forestry. Only when the exercise had started were participants informed that the outbreak scenario centred around the fictitious discovery of pinewood nematode ( Bursaphelenchus xylophilus ) in the Tara National Park in Serbia. As the scenario developed, each team had to organize themselves to manage a number of issues designed to mimic the development of an outbreak over the first month following its detection. It was clear from the feedback from participants that that contingency planning workshop was a valuable exercise for EPPO to conduct and participants highlighted the importance of it to prepare themselves for real‐life situations.